Scale Up Studies on Chemical Modification of Cellulose for Dye Removal (International Journal of Scientific Research in Science and Technology, 2025)
Dialdehyde cellulose (DAC) was prepared through sodium periodate method. The resultant DAC was treated with octylamine to form cellulose Schiff base and it was characterized using various techniques such as FTIR, X-ray diffraction, elemental analysis. TGA was also conducted to find the thermal stability of the cellulose and cellulose Schiff base. Removal of Brilliant blue, Methyl orange and Bromocresol green dyes by cellulose Schiff base was studied and the percent removal of Brilliant blue, Methyl orange and Bromocresol green dyes from their solutions were 100%, 100%, and 81%, respectively. Cellulose Schiff base synthesized in the present investigation exhibits an excellent reusable property.